2022
DOI: 10.3389/fnagi.2022.985386
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram incorporating red blood cell indices to predict post-stroke cognitive impairment in the intracerebral hemorrhage population

Abstract: BackgroundPost-stroke cognitive impairment (PSCI) plagues 20–80% of stroke survivors worldwide. There is a lack of an easy and effective scoring tool to predict the risk of PSCI in intracerebral hemorrhage (ICH) patients. We aimed to develop a risk prediction model incorporating red blood cell (RBC) indices to identify ICH populations at risk of PSCI.MethodsPatients diagnosed with ICH at the stroke center were consecutively enrolled in the study as part of the development cohort from July 2017 to December 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…The subject cohort size ranged from 72 to 22,950. The diagnostic criteria used in the included studies were Mini-Mental State Examination (MMSE) ( 33 ), Montreal Cognitive Assessment (MoCA) ( 34 ) ( n = 5) ( 20 , 21 , 28 , 29 , 31 ), MMSE ( n = 6) ( 12–14 , 18 , 24 , 32 ), MoCA ( n = 6) ( 17 , 19 , 22 , 25–27 ), Center of Cancelation (CoC) ( 35 ) ( n = 1) ( 15 ), Global Deterioration Scale (GDS) ( 36 ) ( n = 1) ( 16 ), Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) ( 37 ) ( n = 1) ( 23 ), and vascular dementia criteria of the AHA/ASA scientific statement ( 38 ) ( n = 1) ( 30 ). The duration of follow-up was predominantly 3 to 12 months, and was 36 years in only one study ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subject cohort size ranged from 72 to 22,950. The diagnostic criteria used in the included studies were Mini-Mental State Examination (MMSE) ( 33 ), Montreal Cognitive Assessment (MoCA) ( 34 ) ( n = 5) ( 20 , 21 , 28 , 29 , 31 ), MMSE ( n = 6) ( 12–14 , 18 , 24 , 32 ), MoCA ( n = 6) ( 17 , 19 , 22 , 25–27 ), Center of Cancelation (CoC) ( 35 ) ( n = 1) ( 15 ), Global Deterioration Scale (GDS) ( 36 ) ( n = 1) ( 16 ), Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) ( 37 ) ( n = 1) ( 23 ), and vascular dementia criteria of the AHA/ASA scientific statement ( 38 ) ( n = 1) ( 30 ). The duration of follow-up was predominantly 3 to 12 months, and was 36 years in only one study ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were 31 models in the included studies, which were constructed based on logistic regression (LR) nomogram ( n = 18) ( 12 , 14–16 , 18 , 19 , 22 , 25 , 26 , 29–32 ), random forest ( n = 1) ( 20 ), ridge regression ( n = 1) ( 23 ), LASSO regression ( n = 1) ( 21 ), mixed effects model ( n = 3) ( 24 ), support vector machine (SVM) classifier ( n = 3) ( 27 ), and decision trees ( n = 3) ( 28 ) ( Table 1 ). Modeling variables were selected using a multivariate approach.…”
Section: Resultsmentioning
confidence: 99%
“…Stroke patients with low hemoglobin levels have been found to harbor increased risks of PSCI. 15 Studies reported that decreased hemoglobin levels might lead to brain hypoxia, mitochondrial dysfunction, and neuronal damage. Patients who have ischemia stroke with hypoxic conditions are much more susceptible to Alzheimer’s disease.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Hemoglobin level is a significant independent predictor of PSCI. 15 Serum albumin is widely considered a surrogate of nutrition where deficiencies in serum albumin have been associated with poorer stroke outcomes, 12 explained in part by an impaired antioxidant capacity to protect neurons from ischemic injury. 18 The geriatric nutritional risk index based on serum albumin has been similarly implicated in PSCI.…”
Section: Introductionmentioning
confidence: 99%
“…8 Existing models to predict PSCI have demonstrated moderate accuracy but are not amenable to large-scale prospective implementation. Published models have largely focused on short-term follow-up (< 6 months) following stroke, [9][10][11] and often include predictors that are not available or easily accessible in electronic health records (EHRs). [10][11][12][13][14] Models that predict PSCI over longer periods may be more useful clinically to allow time for secondary prevention efforts.…”
Section: Introductionmentioning
confidence: 99%